The myth of the ethical consumer - Devinney, Timothy M. (Timothy Michael), 1956-; Auger, Pat.; Eckhardt, Giana M. (Cambridge : Cambridge University Press, 2010)
'Do consumers really care where products come from and how they are made? Is there such a thing as an'ethical consumer'? Corporations and policy makers are bombarded with international surveys purporting to show that most consumers want ethical products. Yet when companies offer such products they are often met with indifference and limited uptake. It seems that survey radicals turn into economic conservatives at the checkout. This book reveals not only why the search for the'ethical consumer' is futile but also why the social aspects of consumption cannot be ignored. Consumers are revealed to be much more deliberative and sophisticated in how they do or do not incorporate social factors into their decision making. Using first-hand findings and extensive research, The Myth of the Ethical Consumer provides academics, students and leaders in corporations and NGOs with an enlightening picture of the interface between social causes and consumption'--
'The Ethical Consumer and Myth The notion of ethical consumers has evolved over the last 25 or more years from an almost exclusive focus on environmental issues to a concept that more broadly incorporates matters of conscience, only to return to its'green' roots with the recent concerns about global climate change'--
Book is accompanied by 1 DVD-ROM, entitled'The myth of the ethical consumer' bearing the same call number and available at Koleksi Media
Includes bibliographical references and index.
System requirements for accompanying DVD-ROM: Windows Media Player or similar; DVD-ROM drive.
Keywords: Consumption (Economics) -- Moral and ethical aspects